2008
DOI: 10.1007/s11104-008-9753-7
|View full text |Cite
|
Sign up to set email alerts
|

Root, mycorrhiza and earthworm interactions: their effects on soil structuring processes, plant and soil nutrient concentration and plant biomass

Abstract: Earthworms, arbuscular mycorrhiza fungi (AMF) and roots are important components of the belowground part of terrestrial ecosystem. However, their interacting effects on soil properties and plant growth are still poorly understood. A compartmental experimental design was used in a climate chamber in order to investigate, without phosphorus (P) addition, the single and combined effects of earthworms (Allolobophora chlorotica), AMF (Glomus intraradices) and roots (Allium porrum) on soil structure, nutrient concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 41 publications
4
48
1
1
Order By: Relevance
“…Development of soil structure from micro-to macro-scale is a function of interacting physical forces of soil water content, actions of large biota like plant roots and earthworms, presence of organic matter in the soil and tillage 10 . The most prominent effect of the earthworm is on the reorganization of soil structure while moving through the soil, feeding on the soil 11 and release of material due to their low assimilation efficiency.…”
Section: Soil Structural Developmentmentioning
confidence: 99%
“…Development of soil structure from micro-to macro-scale is a function of interacting physical forces of soil water content, actions of large biota like plant roots and earthworms, presence of organic matter in the soil and tillage 10 . The most prominent effect of the earthworm is on the reorganization of soil structure while moving through the soil, feeding on the soil 11 and release of material due to their low assimilation efficiency.…”
Section: Soil Structural Developmentmentioning
confidence: 99%
“…However, if carbon and nitrogen mineralization were observed in the studied urban and alluvial soils with respect to earthworm activity, available phosphorus content did not increase in the urban soil material after one and three months of incubation. In the literature, it is generally admitted that in many soils earthworms increase available phosphorus content through the stimulation of soil microorganisms (Suarez et al, 2004;Milleret et al, 2009;Le Bayon et al, 2011) but little is known about the effect of earthworm activity on soil processes in urban soils. Stroo andJenks (1982, inBullock andGregory, 1991) reported similarly lower available phosphorus content in mine soils compared to native soils after twenty years of soil reclamation.…”
Section: Endogeic Earthworms As Actors Of the Soil Organic Matter Dynmentioning
confidence: 99%
“…It is for example unclear if the effects of endogeic earthworms, whose roles in soil organic matter (SOM) transformation and soil structuration are well document-ed in natural and agricultural soils (Edwards and Bohlen, 1996;Lavelle and Spain, 2001;Edwards, 2004;Bernard et al, 2011;Capowiez et al, 2012), are similar in urban soils. Few studies reported the burrowing ac-tivity of earthworms under controlled conditions in different urban soils (Nahmani et al, 2005;Milleret et al, 2009;Pey et al, 2013)but no com-parison exists between alluvial and urban soil materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that interaction between organic matter input and plant roots improves aggregate stability in degraded land (Caravaca et al, 2002). In addition, Milleret et al (2009) confirm that water stable aggregates, available phosphor, available nitrogen and OC may control the effects of organism interactions, such as those between earthworms and mycorrhiza fungi. Understanding the effects of organic matter content and soil organisms is necessary to optimize the benefits on soil structure.…”
Section: Introductionmentioning
confidence: 58%